Assessment of Serum Calcium, Serum Iron and Nutritional Status among Under-Five Children in Six Municipalities of Abidjan District, Côte d’Ivoire - Koné, Mohamed B.; Traoré, Souleymane; Brou, Kouakou; Edith, Agbo A.; Dago, Gnakri (International Journal of Child Health and Nutrition, 2014)
Malnutrition occurs in various forms in the world, especially in African countries. It affects two-thirds of the children in sub-Saharan Africa. In addition to the protein-energy malnutrition (PEM), micronutrient deficiencies also affect many children. The aim of this study was to evaluate the nutritional status, serum iron and serum calcium among under-five children. This study was conducted on a cohort from 480 children in six municipalities of Abidjan: Abobo, Cocody, Koumassi, Marcory, Treichville and Yopougon. A blood sample and anthropometric measurements (weight, height) were performed to determine the hematological profile and nutritional status of children. The results showed that stunting was the most widespread form of malnutrition among children surveyed. Depending on age, children from 0 to 6 months have a low prevalence of PEM than those from 7 to 59 months: wasting (1.2% vs 3.5%), stunting (8.6% vs 25.2%) and underweight (3.4% vs 10.7%). Also, the results reveal a lowest serum iron (µmol/l) among children from low households income (9.77 ± 2.4), illiterate mothers (8.92 ± 1.3) compared to those from mothers with a high level of education (21.75 ± 4.1) and high living standard (21.28 ± 2.1). There was no notable difference (p>0.05) between serum calcium whatever socio-demographic parameters considered. The parameters under study such as nutritional status, serum calcium and serum iron have shown a variation of malnutrition in Abidjan.